Foliar application of microdoses of sucrose to reduce codling moth Cydia pomonella L. (Lepidoptera: Tortricidae) damage to apple trees. Issue 10 (25th February 2016) - Arnault, Ingrid; Lombarkia, Nadia; Joy‐Ondet, Sophie; Romet, Lionel; Brahim, Imene; Meradi, Rahma; Nasri, Ardjouna; Auger, Jacques; Derridj, Sylvie
Abstract: BACKGROUND: The effects of foliar applications of microdoses of sucrose to reduce the damage by the codling moth have been reported from nine trials carried in France and Algeria from 2009 to 2014. The activity of sucrose alone was assessed by comparison with an untreated control and some treatments with the Cydia pomonella granulovirus or a chemical insecticide. The addition of sucrose to these different treatments was also investigated. RESULTS: The application of sucrose at 0.01% reduced the means of infested fruits with a value of Abbott's efficacy of 41.0 ± 10.0%. This involved the induction of resistance by antixenosis to insect egg laying. Indeed, it seems that acceptance of egg laying on leaves treated with sucrose was reduced. The addition of sucrose to thiacloprid improved its efficacy (59.5% ± 12.8) by 18.4%. However, the sucrose had no added value when associated with C. pomonella granulovirus treatments. CONCLUSION: Foliar applications of microdoses of sucrose every 20 days in commercial orchards can partially protect against the codling moth. Its addition to thiacloprid increases the efficacy in integrated control strategies, contrary to C. pomonella granulovirus treatments. This work opens a route for the development of new biocontrol strategies. © 2016 Society of Chemical Industry